2014
DOI: 10.3390/ijerph111212915
|View full text |Cite
|
Sign up to set email alerts
|

Rat Lung Response to PM2.5 Exposure under Different Cold Stresses

Abstract: Ambient particulate matters and temperature were reported to have additive effects over the respiratory disease hospital admissions and deaths. The purpose of this study is to discuss the interactive pulmonary toxicities of cold stress and fine particulate matter (PM2.5) exposure by estimating inflammation and oxidative stress responses. 48 Wistar male rats, matched by weight and age, were randomly assigned to six groups, which were treated with cold stress alone (0 °C, 10 °C, and 20 °C (Normal control)) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 31 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…Cold exposure was also found to increase the frequency of heart rate variability and ventricular ectopic beats 22. In addition, exposure to cold caused significant increase of inflammatory cytokines and methane dicarboxylic aldehyde and decline of superoxide dismutase (SOD) and glutathione peroxidase activity,23 and the genes involved in the hypoxia-inducible factor signalling pathway were activated in which oxidative stress-associated genes were significantly upregulated, including SOD2 and epoxide hydrolase 2 24. On the other hand, exposure to hot weather may induce profound physiological changes, such as increase in blood viscosity and cardiac output leading to dehydration, hypotension, surface blood circulation increase and even endothelial cell damage 25.…”
Section: Discussionmentioning
confidence: 99%
“…Cold exposure was also found to increase the frequency of heart rate variability and ventricular ectopic beats 22. In addition, exposure to cold caused significant increase of inflammatory cytokines and methane dicarboxylic aldehyde and decline of superoxide dismutase (SOD) and glutathione peroxidase activity,23 and the genes involved in the hypoxia-inducible factor signalling pathway were activated in which oxidative stress-associated genes were significantly upregulated, including SOD2 and epoxide hydrolase 2 24. On the other hand, exposure to hot weather may induce profound physiological changes, such as increase in blood viscosity and cardiac output leading to dehydration, hypotension, surface blood circulation increase and even endothelial cell damage 25.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicates a possible mechanistic interaction between these exposures in RA. While there are studies that attempt to delineate the effect of acute/short-term cold exposure on the immune system, [15][16][17] studies that investigate the impact of long-term exposure to cold environment in conjunction with high physical workload on the immune system are scarce. Whether exposure to long-term cold work environment causes aberrant Rheumatoid arthritis immune reactions resulting into a chronic inflammatory disease like RA remains elusive.…”
Section: Rmd Openmentioning
confidence: 99%
“…Toxicological studies have demonstrated that chronic exposure to traffic related air pollution, such as particulate matter with a diameter of 2.5 microns or less (PM 2.5 ) can trigger an inflammatory response in rats (Luo et al 2014; Xu et al 2008; Ying et al 2015) and humans (Ostro et al 2014). To date, there have been only a few studies investigating the effects of long term PM 2.5 exposure and bronchiolitis (de Pablo-Romero et al 2015; Karr et al 2007; Karr et al 2009a; Karr et al 2009b) or OM (Brauer et al 2006; MacIntyre et al 2011; MacIntyre et al 2013), indicating evidence of a possible association (Brauer et al 2006; Karr et al 2007; MacIntyre et al 2011).…”
mentioning
confidence: 99%